Therapeutic Effects of a Newly Developed 3D Magnetic Finger Rehabilitation Device in Subacute Stroke Patients: A Pilot Study - Sung-Hoon Kim; Dong-Min Ji; Chan-Yong Kim; Sung-Bok Choi; Min-Cheol Joo; Min-Su Kim (Brain Sciences, 2022)
We developed a magnetic-force-based three-dimensional (3D) rehabilitation device that can perform motor rehabilitation treatment for paralyzed fingers, regardless of upper extremity movement and position, and investigated the therapeutic effects of the device. An end-effector type rehabilitation device that can generate magnetic fields in three directions was developed using electromagnets and permanent magnetics. A double-blinded randomized controlled pilot study was conducted with a total of 12 patients. The intervention group had rehabilitation treatment using the developed magnetic finger rehabilitation device for 30 min a day for four weeks. The control group underwent exercise rehabilitation treatment. The control group received conventional occupational therapy on the upper limbs, including hands, from an occupational therapist, for the same amount of time. Adverse effects were monitored, and the patient’s sensory or proprioceptive deficits were examined before the intervention. No participants reported safety concerns while the intervention was conducted. The Wolf Motor Function Test (WMFT) scores were significantly improved in the intervention group (from 13.4 ± 3.6 to 20.9 ± 4.0 points) compared to the control group (from 13.1 ± 4.0 to 15.2 ± 3.8 points) (p = 0.016). The patients in the intervention group (from 88 ± 12 to 67 ± 13 s) showed greater improvement of WMFT times compared to the control group (from 89 ± 10 to 73 ± 11 s) (p = 0.042). The Manual Function Test and the upper limb score of the Fugl-Meyer Assessment were significantly improved in the intervention group compared with the control group (p = 0.038 and p = 0.042). The patients in the intervention group also showed significantly greater enhancement of the Korean version of the modified Barthel Index than the control group (p = 0.042). Rehabilitation treatment using the 3D magnetic-force-driven finger rehabilitation device helped improve finger motor function and activities of daily living in subacute stroke patients.